Impacts of Bush Encroachment on Wildlife Species Diversity, Composition, and Habitat Preference in Ol Pejeta Conservancy, Laikipia, Kenya. (6th December 2017) - Kavwele, Cyrus M.; Kimanzi, Johnstone K.; Kinyanjui, Mwangi J.
Abstract : Savannah ecosystems are currently facing a biome shift that changes grasslands to woody dominated landscapes, attributable to habitat degradation. In Ol Pejeta Conservancy (OPC), Euclea divinorum, an unpalatable and invasive woody species, is expanding to former savannah ecosystems with potential effects on herbivores key resources, wildlife species diversity, composition, and habitat use. We investigated wildlife species diversity, composition, and habitat preference or avoidance by wildlife in the conservancy. Infrared camera traps were deployed at the centroids of 2 km by 2 km, 50 cm above ground surface for 14 days and nights with 9 camera traps in each habitat type. Shannon wiener index revealed that wildlife species diversity was highest in E. divinorum dominated habitats and lowest in open grassland. Hierarchical Cluster Analysis revealed level of similarity in wildlife species composition between E. divinorum and mixed bushland. Jacobs index revealed that E. divinorum and mixed bushland were avoided by all guilds; however E. divinorum was significantly avoided while A. drepanolobium and open grassland were both preferred by all guilds. However, A. drepanolobium dominated habitats were significantly preferred compared to open grasslands. The findings are useful in management of sustainable ecosystems.